Imagining the smart city through smart grids? Urban energy futures between technological experimentation and the imagined low-carbon city - Leslie Quitzow; Friederike Rohde (Urban Studies, 2022)
Current imaginaries of urban smart grid technologies are painting attractive pictures of the kinds of energy futures that are desirable and attainable in cities. Making claims about the future city, the socio-technical imaginaries related to smart grid developments unfold the power to guide urban energy policymaking and implementation practices. This paper analyses how urban smart grid futures are being imagined and co-produced in the city of Berlin, Germany. It explores these imaginaries to show how the politics of Berlin's urban energy transition are being driven by techno-optimistic visions of the city's digital modernisation and its ambitions to become a `smart city'. The analysis is based on a discourse analysis of relevant urban policy and other documents, as well as interviews with key stakeholders from Berlin's energy, ICT and urban development sectors, including key experts from three urban laboratories for smart grid development and implementation in the city. It identifies three dominant imaginaries that depict urban smart grid technologies as (a) environmental solution, (b) economic imperative and (c) exciting experimental challenge. The paper concludes that dominant imaginaries of smart grid technologies in the city are grounded in a techno-optimistic approach to urban development that are foreclosing more subtle alternatives or perhaps more radical change towards low-carbon energy systems.
Keywords: 300; smart city; smart grid; urban imaginary; urban laboratories